Metode Menghafal Al-Qur’an untuk Anak Tunalaras dengan Metode Fasih Al-Qur’an (Studi Kasus di Pondok Pesantren Ainul Yakin Yogyakarta) - Mahmud Rifaannudin; Syifa’ Nadia Rizka; Ahmad Fadly Rahman Akbar; Rezki Kaulan Maisurah (Studia Quranika, 2024)
A unique technique is needed for some people to memorize the Qur'an, especially children who struggle emotionally. Certain techniques designed for Qur'anic memorization are inapplicable to children with impairments. Therefore, understanding the Qur'an requires a unique approach, just as it does for children in general. Ainul Yakin Islamic Boarding School Yogyakarta gives children with disabilities a special method to be applied in memorizing the Qur'an called the "Fasih Al-Qur'an" method. This study aimed to find out the "Fasih Al-Qur'an" method to learn the Qur'an for students with emotional disorders at the Ainul Yakin Islamic Boarding School in Yogyakarta. This research is field research with qualitative research methods. Data collection techniques with three steps observation, interview, and documentation. Field qualitative data processing and analysis techniques using four methods data collection, data reduction, data presentation, and conclusion. The results of this paper show that the method of memorizing the Qur'an for children with disabilities, the "Fasih Al-Qur'an" method is proof of the ease of remembering the Qur'an because the Qur'an is for all humans without any differences, especially children with emotional disorders. Habitual learning in boarding schools makes children accustomed to memorizing the Qur'an, and negative behavior will be reduced